Population genetics and biophysical modeling inform metapopulation connectivity of the Caribbean king crab Maguimithrax spinosissimus - Baeza, Juan Antonio (2019)
Marine organisms with a short pelagic larval duration (PLD) are assumed to display significant population structure given low long-distance dispersal ability. For the wider Caribbean, theoretical and empirical considerations suggest that species with short PLDs inhabiting each of the following areas should be genetically distinct: Costa Rica (CR), Mexico (MX), and Florida Keys (FL-K), USA. This study tested the hypothesis of significant genetic differentiation in Maguimithrax spinosissimus populations across the wider Caribbean using a combination of biophysical modeling and population genetics. Biophysical modeling predicted dissimilar connectivity patterns among CR, MX, and FL-K depending upon assumed PLD. Eight days of dispersal only provided rare connections from MX to FL-K, and low likelihood multi-generational connections between CR and FL-K. In turn, 12 d of dispersal was sufficient to connect MX to FL-K through direct and indirect routes in biophysical models, but CR and FL-K remained connected only through multiple generational steps. After 16 d of dispersal, direct connections between CR and FL-K may occur, and by 20 d of dispersal, connections are likely between all sampled patches. Population genetic analyses based on partial sequences of the mtDNA 12S, 16S, and COI genes denoted the existence of a single, relatively high-frequency haplotype shared among all 3 populations, which suggests a longer PLD than predicted by laboratory study. In turn, an analysis of molecular variance and pairwise FST values demonstrated significant genetic differentiation among the studied populations. Altogether, the above information suggests low to moderate connectivity among populations in M. spinosissimus. Subpopulation split predictions suggest multi-generational or stepping-stone connectivity between CR and both MX and FL-K, and provides a framework for understanding the structure of M. spinosissimus metapopulations throughout the region. Overall, this study agrees with the notion of significant population structure in marine species with lower dispersal ability.